Penciptaan Buku Ilustrasi Religius âKelahiran Yesus Kristusâ Melalui Wayang Wahyu Dengan Teknik Aquarel Sebagai Upaya Mengenalkan Budaya Lokal - Putri, Bella Arifanda; Budiardjo, Hardman; Riyanto, Darwin Yuwono (Jurnal Art Nouveau, 2016)
AbstractWayang Wahyu is the one of local culture that owned by Indonesian Nation, which is a performance art with media images or mock that made by leather and wood that tell the stories from Old Testament to the New Testament. But in a real situation, Wayang Wahyu is now being forgeted because so many incoming foreign culture that appear, a lack of awareness that known how importance the local culture, and required an exciting the new media to delivering the message of the Bible for children. Based on observation, interview, and literature, found the fact that children are less familiar with traditional art of Wayang Wahyu. Therefore, the purpose of this creation is to revive the existence of Wayang Wahyu for introduce to children. The method that used to create an illustrated book of the Bible is using the characters by puppet in order to make a sense of belonging and not effected the foreign taste in the message of Bible stories that will be delivered, equipped with two languages (Indonesian â Javanese language), interactive pages, also supported some promotional media like mini X-banners, display character, key chains, bookmarks, stickers and pins. Through this illustrated book of the Bible, can be used the attractive preaching for Christianity and introduce the Wayang Wahyu as local cultural to the children. Keyword: Wayang Wahyu, Puppet, Book Illustration, Birth of Jesus Christ, Arts and Culture, Christian, Local Culture, Traditional Arts.